Tongkol Fishery Management using an Ecosystem Approach through an Assessment of the Status of Fish Resource Domains in the West Season Landed on Segara Kusamba Beach, Bali: Pengelolaan Perikanan Tongkol dengan Pendekatan Ekosistem melalui Penilaian Status Domain Sumber Daya Ikan pada Musim Barat yang Didaratkan di Pantai Segara Kusamba, Bali - Desak Putu Permathasari; I Wayan Restu; Made Ayu Pratiwi Pratiwi (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2021)
Segara Kusamba Beach, Klungkung, Bali is a beach with the main catch fishery product, namely Tongkol Fish. The high level of tongkol fishing activities on Segara Kusamba Beach must be balanced with proper management so that Tongkol Fish Resources remain sustainable. So a research was carried out that aims to determine the status of the utilization of tongkol fishery resources landed on Segara Kusamba Beach with an ecosystem approach to the fish resource domain. The research was conducted in November 2019-January 2020. Data was collected by direct observation and interviews. Data analysis for each indicator was carried out using a multi-criteria analysis approach, then composite index assessment and visualized with a flag model. The results showed that the tongkol fish Resource domain in Segara Kusamba Beach got a light green flag model with a good status and got a composite value of 69.43. The trend indicator for fish size is relatively constant, the indicator for the proportion of yuwana fish is 44% of the total catch, the 95% species composition indicator is dominated by tongkol as the target fish, the indicator for range collapse of fish resources is increasingly difficult in determining the fishing area, and on indicators There are no ETP species caught on the Segara Kusamba Beach. So that it can provide advice on capture fisheries management in the form of fishing period management, improved mesh size and better cooperation between steakholders and fishermen in order to create better tongkol fishing in Segara Kusamba Beach, Klungkung.